Controlling factors and evolution of reservoirs in continental rift lacustrine carbonate factory: insight from the cretaceous ITP-BVE formation in Brazil’s Santos Basin - Yang, Mengying; Tan, Xiucheng; Xu, Fang; Hao, Duo; Zhao, Junfeng; Li, Chenqing; Huang, Jixin; Li, Peijia (Frontiers in Earth Science, 2025)
The Cretaceous Itapema and Barra Velha Formations in Brazil’s Santos Basin represent a rare giant rift lacustrine carbonate factory with considerable potential for oil and gas exploration. Through a comprehensive petrological and petrophysical analysis of field A in Santos Basin, this study clarifies the reservoir properties and distribution of this lacustrine carbonate facies and further investigates the controlling factors and differential evolution of lacustrine carbonate reservoirs. The main research results are as follows: (1) The Itapema Formation is characterized by bioclastic limestones that predominantly feature primary interparticle pores. As the alkalinity and salinity of the lake water gradually increased, the reservoir rocks of the Barra Velha Formation evolved into shrubstones and intraclastic limestones, with reservoir spaces comprising growth-framework pores and interparticle pores. (2) High-quality reservoirs are distributed regularly and cyclically below the exposure surfaces of high-frequency cycles. The quality of the reservoir exhibits an improvement from the bottom to the top of upward-shallowing sequences. These sequences, which are generally stacked vertically, enhance the heterogeneity of the reservoir. (3) Fluctuations in lake levels have facilitated the process of penecontemporaneous karstification, resulting in the formation of numerous dissolved pores and vugs. Generally, karstification enhances the quality of reservoirs; however, excessive karstification at the tops of cycles may result in the infilling of clay within breccias, consequently diminishing reservoir quality. (4) Multiple magmatism during rift evolution exert a dual control on reservoir space. Intense silicification can lead to the complete filling of pores and fractures with siliceous cement, thereby compromising reservoir spaces. However, rim-like siliceous cements formed during syn-depositional magmatism effectively isolate pore spaces, inhibiting material exchange during shallow burial. This process achieves a balance between dissolution and precipitation that ultimately preserves porosity. In general, reservoirs within the Itapema Formation exhibited a developmental trajectory that transitioned from superior primary porosity to karst-enhanced intraparticle porosity, ultimately resulting in rim-like siliceous cements that preserved the pores. In contrast, the reservoirs of the Barra Velha Formation experienced a different evolutionary process, commencing with the differentiation of matrix porosity, which was subsequently increased by karstification. During the penecontemporaneous and burial stages, the pores infilled with silica and dolomite cements. This study presents a systematic analysis of the reservoir properties and diagenetic evolution of this set of lacustrine carbonate rocks. It contributes to the theoretical understanding of lacustrine carbonate deposition and provides valuable references for carbonate reservoir exploration in rift lake basins.